2022
DOI: 10.1530/eje-21-1221
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver fat associates with severe metabolic perturbations in low birth weight men

Abstract: Objective: Ectopic liver fat deposition, resulting from impaired subcutaneous adipose tissue expandability, may represent an age-dependent key feature linking low birth weight (LBW) with increased risk of Type 2 diabetes (T2D). We examined whether presumably healthy early middle-aged, non-obese LBW subjects exhibit increased liver fat content, whether increased liver fat in LBW associates with severity of dysmetabolic traits, and finally whether such associations may be confounded by genetic factors. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…After 17 weeks of HFD, the body weight was not significantly different between the two groups (Figure 1C). Several clinic studies suggested that LBW individuals on HFD showed an increased trend toward serum TC and liver fat compared to NBW on HFD (18)(19)(20). Animal studies also showed that LBW is a risk factor for increased hepatic cholesterol (21).…”
Section: Discussionmentioning
confidence: 99%
“…After 17 weeks of HFD, the body weight was not significantly different between the two groups (Figure 1C). Several clinic studies suggested that LBW individuals on HFD showed an increased trend toward serum TC and liver fat compared to NBW on HFD (18)(19)(20). Animal studies also showed that LBW is a risk factor for increased hepatic cholesterol (21).…”
Section: Discussionmentioning
confidence: 99%
“…The study included 48 healthy Caucasian males born at gestational weeks 39–41 between 1979 and 1980 and recruited from the Birth Registry at the Danish Health Data Authority, as described previously [ 3 ]. In total, 26 individuals were born with a birth weight < 10th percentile (LBW) and 22 individuals were age- and BMI-matched controls born with a birth weight between the 50th and 90th percentile (NBW).…”
Section: Methodsmentioning
confidence: 99%
“…Low-birth-weight (LBW) is a marker of an adverse fetal environment and is associated with an increased risk of developing type 2 diabetes (T2D) [ 1 , 2 ]. We recently reported that 20% of non-obese (BMI < 30 kg/m 2 ) LBW individuals with a mean age of 38 years exhibit previously unrecognized non-alcoholic fatty liver disease (NAFLD), supporting the hypothesis of ectopic fat deposition as a key pathophysiological feature underlying development of T2D in individuals born with a LBW [ 3 , 4 , 5 , 6 ]. The LBW individuals with NAFLD were characterized by elevated hepatic insulin resistance, fasting levels of insulin, C -peptide, and triglycerides (TG), as well as elevated plasma levels of leptin and GLP-1, compared with both LBW and normal-birth-weight (NBW) individuals without NAFLD [ 3 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both early and late life stimuli are capable of creating a metabolic environment that leads to epigenomic programming or “memory” in tissues. One recent example of this is the observation that low birthweight infants have higher liver fat and earlier onset of prediabetes compared to normal birth weight counterparts [ 65 ]. These findings suggest that differences in metabolic health across various stages of life have residual effects.…”
Section: Knowledge Gaps In Aging and Exercise Response Variationmentioning
confidence: 99%